Mengamati Perilaku Merokok Pada Masyarakat Batang Kilat, Kelurahan Sei Mati, Medan Labuhan Tahun 2023 N - Nurhayati, Nurhayati; Andina, Adelia; Wijaya, Arini Aisyahfira; Siregar, Fatimah Azzahra; Andini, Fauziah Siti; Nurcholis, Hari; Irsyad, Iqbal; Alifah, Syafirda (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Various This research was conducted aiming to determine the percentage of people who actively smoke and to prove how the behavior of coastal communities in Sei Mati Medan Labuhan Village regarding health. To achieve this goal, the researcher used a quantitative descriptive method, which is a research methodology by submitting questionnaires to informants or the public. This was done to calculate, describe, and present the community's figures regarding smoking behavior. The analysis technique used was interviews with questions that had been arranged in a questionnaire. The results showed that of the 30 samples taken from coastal communities, 60% of the respondents were active smokers, the majority of whom were 20 years old. Factors supporting the counseling strategy on public health in the Sei Mati Medan Labuhan Subdistrict are due to the high number of active smokers in coastal areas and are related to behavior drivers in the community itself. Keywords: Healthy behavior, Coastal Society, Cigarettes, Methods